Piptadenia Africana: Enhances Weight Gain, Oxidative Stress, Hyperlipidemia in Normal and Hypercholesterolemic Male Wistar Rat - Onyenibe, Nwozo Sarah; Emmanuel, Oyinloye Babatunji (Journal of Food and Pharmaceutical Sciences, 2017)
Poyphenol rich stem bark of Piptadenia africana (PA) is used to treat gastric pain, fever, cough and we evaluated the effect of daily, continual intake of PA for eight weeks in hypercholesterolemic rats. Thirty six rats were divided into six equal groups, A (positive-control); B (cholesterol) (negative-control); C (100 mg/kg bwt PA); D (200 mg/kg bwt PA); E (cholesterol+100 mg/kg bwt PA) and F (cholesterol+200 mg/kg bwt PA). Corn oil served as vehicle for both cholesterol (40 mg/kg/0.3ml) and PA. PA caused increased weight-gain, no enlarged organs but decreased their protein concentrations relative to control. Serum triglyceride, total cholesterol and LDL-cholesterol were elevated in PA only and PA co-treated cholesterol rats relative to both control groups, culminating in high atherogenic index. Lipidperoxidation increased dose dependently while glutathione-peroxidase, glutathione-S-transferase, reduced glutathione, superoxide dismutase and catalase decreased in PA treated groups relative to controls. Histological examination revealed necrosis of hepatocytes in groups D and moderate coagulation of necrosis of tubules of renal medulla in C. Continuous usage of PA may not be totally safe as it enhances weight gain, unhealthy lipid profile, increase chances of cardiovascular disease, elicits oxidative stress and induces organ toxicity.Â Key words: atherogenic-index, lipidperoxidation, lipid profile, organ toxicity, Piptadenia africana.